All-Optical NOT Logic Gate Based on Photonic Crystals - Majid Ghadrdan; Mohammad Ali Mansouri-Birjandi (International Journal of Electrical and Computer Engineering (IJECE), 2013)
A novel scheme for implementation of all-optical NOT logic gate based on photonic crystal ring resonator has been proposed. Photonic crystal is comprised of two-dimensional square lattice of dielectric rods in air substrate. Indium phosphide with a refractive index of 3.1 is adopted as the material of the rods. The finite different time domain (FDTD) and plane wave Expansion (PWE) methods are used to analyze the behavior of the structure. The simulation results show that the contrast ratio is 10.97dB for NOT gate. Moreover, the operational wavelength of the input ports is 1.55µm. Since the structure has a simple geometric shape with clear operating principle, it is potentially applicable for photonic integrated circuits.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2909